Comment on “Usefulness of the FDG PET/CT in the management of cystic echinococcosis: A pilot study” - Manciulli, T.; Tamarozzi, F.; D'Alessandro, G.L.; Gruener, B.; Brunetti, E. (Acta tropica, 2023)
•Cystic echinococcosis is a neglected disease with a complex clinical management, requiring interdisciplinary knowledge.•Currently, no uninvasive method to assess the biological viability of echinococcal cysts is available.•The study presents PET-CT as a potential tool for viability assessment based on previous studies on alveolar echinococcosis but the studied cohort appears inadequate to such aim.•Based on knowledge on the use of PET-CT in alveolar echinococcosis, a  more rational aim would be to evaluate the performance of PET-CT as a mean to assess complications, rather than cyst viability.